THE USE OF SKIMMING AND SCANNING TECHNIQUES FOR COLLEGE STUDENTS IN READING CLASS - Wahyuningsih, Destri (Menara Ilmu, 2018)
Reading class refers to the readers’ ability to understand the information of reading text.Skimming and Scanning are reading techniques that use rapid eye movement and keywordsto move quickly through text for slightly different purposes. Skimming is reading rapidly inorder to get a general overview of the material (general topic and main ideas). Scanning isreading rapidly in order to find specific facts. By applying skimming and scanning techniquesin teaching reading, the college students will be easier to understand about reading text andquickly to get information in a few minutes.Keywords: the importance of reading, skimming and scanning techniques, skimming andscanning for understanding, the benefits of skimming and scanning.